Computer‐assisted zygoma reconstruction with vascularized iliac crest bone graft. Issue 4 (6th November 2013) - Modabber, Ali; Gerressen, Marcus; Ayoub, Nassim; Elvers, Dirk; Stromps, Jan‐Philipp; Riediger, Dieter; Hölzle, Frank; Ghassemi, Alireza
Abstract Background The reconstruction of zygoma is a challenge with regard to aesthetic and reconstructive demands. Methods Pre‐operative CT data were imported into specific surgical planning software. The mirror‐imaging technique was used. A surgical guide transferred the virtual surgery plan to the operation site, whereby it fitted uniquely to the iliac donor site. A postoperative CT scan was obtained for comparing the actual postoperative graft position and shape with the pre‐operative virtual simulation. Results A mean difference of 0.71 mm (SD ± 1.42) for the shape analysis and 3.53 mm (SD ± 3.14) for the graft position was determined. The calculation of the closest point distance showed a surface deviation of < 2 mm for the shape analysis with 83.6% of values and for the graft position with 35.7% of values. Conclusion Virtual surgical planning is a suitable method for zygoma reconstruction with vascularized iliac crest bone graft, with good accuracy for restoring the three‐dimensional anatomy. Copyright © 2013 John Wiley & Sons, Ltd.